Modelling the Performance Characteristics of Four Stroke Internal Combustion Renault Engine Cycle using Matlab Simulation Tool - Ikpe, A. E.; Owunna, I. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The trends in Internal Combustion Engine (ICE) cycle is gradually changing due to the quest for optimum performance, efficiency and zero emission level which are often achieved through a series of experimental procedures. To reduce the huge experimental cost, time and resources, MATLAB 2018b was employed in the modelling and simulation process of a four stroke internal combustion Renault engine (Mercedes-Benz 250SE) W108 model. The displaced volume was 4.65x10-4 mm3 (4.65x10-7 cm3) while the minimum volume occupied by the charge was 0.5x10-4 mm3 (5x10-8). Moreover, the maximum velocity occurred at a crank angle of 72º, having a value of 19.65 m/s while the minimum velocity occurred at a crank angle of 288º with a value of -19.65 m/s. However, maximum cylinder pressure of 28 bar was observed at crank angle of 20º, followed by gradual decline up to 0.2 bar at subsequent crank angles of 100, 200, 300º. The results showed that maximum peak pressure between simulated data and experimental data were 5347 and 5320 KPa, while maximum spark pressure in cylinder before combustion between simulated data and experimental data were 1849 and 1730 KPa. In addition, highest crank angle at maximum pressure for simulated and experimental data were 30 and 22º. It has been established that developing mathematical models to simulate IC engine operation cycles can help offset the cost, time and resources required for experimental set up, testing and data acquisition from the engine.